Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 2 - Review: 46

Answer

-4

Work Step by Step

"Double the sum of a number and 6" translates to 2(x + 6). "the opposite of the number" translates to -x. Therefore, the equation is 2(x + 6) = -x Solve for x: 2x + 12 = -x 3x + 12 = 0 3x = -12 x = -4
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.